KEBEBASAN BERAGAMA DAN MURTAD DALAM ISLAM: Aplikasi Teori Kontekstual terhadap Ayat-ayat Riddah dalam al-Qur’an - Zulhamdani Zulhamdani (STAI Darul Kamal NW Kembang Kerang, 2021)
This study started from the Islamic understanding of religious freedom for mankind. The Qur'an does not teach compulsion for anyone to convert to Islam. However, what if the followers of Islam themselves leave their religion? Is religious freedom still sustainable? Or are there prohibitions and punishment for those who leave Islam? For this reason, the authors analyze parallel texts between the Qur'an, hadith and historical sources with the contextual approach developed by Abdullah Saeed. Thus, it will be revealed how the attitude of the Prophet Muhammad and his companions towards apostates. So, the stigma of Islam which is accused of being the religion of murderous will be explored and answered contextually.